Physiological signal transduction from the photosynthetic apparatus in the green alga Dunaliella salina - Logie, Malcolme Ronald Ruxton (Rhodes University, Faculty of Science, Department of Biochemistry, Microbiology and Biotechnology, 1995)
The transduction of stress signals in plants is known to involve complex hysiological responses. In D. salina a range of stresses results in hyperaccumulation of ft-carotene and an understanding of stress responses in this organism has important biotechnological implications. In this thesis an attempt was made to elucidate the physiological components involved and establish a role for pH in response to high light stress. In order to achieve this the effect of high light stress on photosynthesis and cell productivity was measured. Results showed that photosynthetic carbon assimilation, oxygen evolution and cellular productivity was initially inhibited by exposure to high light intensities, but this inhibition was transient and was overcome by a rapid increase in all three parameters. The response of the carbon pool intermediates was also investigated. It was shown that on exposure to high light ft-carotene declined but then showed a rapid increase after about 4 hours of exposure. It was also demonstrated that the initial loss of ft-carotene was due to loss of this pigment from the photosynthetic pigment bed and that the hyper-accumulation of ft-carotene was due to accumulation of ft-carotene in lipoidal globules located in the chloroplast stroma. It was further demonstrated that there was mass movement of carbon in the xanthophyll cycle shortly after exposure to high light. This was characterized by the de-epoxidation of violaxanthin to antheraxanthin with a further de-epoxidation to zeaxanthin, thereby decreasing the epoxidation state of the cycle. Furthermore, it was shown that there was relocation of carbon from violaxanthin to the plant growth regulator abscisic acid. It was also shown for the first time in D. salina that the production of ft-carotene and operation of the epoxidation state of the xanthophyll cycle has a periodicity which is established after exposure to successive cycles of a light regime. Chlorophyll fluorescence was used together with well established ammonia stress responses to acquire a general overview of energy dissipation from the photosynthetic pigment bed. In conjunction with an understanding of xanthophyll cycle operation during exposure to high light stress it has been possible to establish a relationship between chlorophyll florescence, xanthophyll cycle operation and intracellular pH. It was also shown using chlorophyll fluorescence that after 4 hour exposure to high light a maximum fluorescence peak could no longer be induced indicating a transition at about this point from a state of reversibility to commitment of the full stress response. Nuclear magnetic resonance was used to follow intracellular pH fluxes during exposure to high light. A novel technique was developed for studying photosynthetically active organisms in the dark using nuclear magnetic resonance. These results showed that on exposure to high light stress there is rapid acidification of the chloroplast stroma and to a lesser degree of the acidic vacuole. The pH of these compartments is re-established after about 4 hours which is co-incident with the onset of fl-carotene hyper-accumulation and the loss of the induction of the chlorophyll fluorescence peak indicating an intimate relationship for fl-carotene, chlorophyll fluorescence, xanthophyll cycle operation and pH. The results from this study allow for the proposal of a general physiological stress transduction response mechanism for D. salina which is common for a range of different stresses and where intracellular pH plays a central role.
Keywords: Cellular signal transduction; Photosynthesis -- Research; Green algae; Dunaliella